A study on the correlation of clinical and ultrasonography diagnosis with histopathological outcome in cases of hysterectomy - Saha, Debapriya; Parikh, Prince; Thakkar, Nimesh Bharatkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hysterectomy is the most commonly performed gynaecological operation throughout the world due to different causes of pelvic pathology. Fewer studies have been performed describing the relationship between preoperative clinical, ultrasonological diagnosis and histopathological outcome. Methods: Authors report 100 cases with benign gynecological disorders who underwent hysterectomy. Authors excluded malignant cases from the study. A preoperative diagnosis was formed based on clinical and ultrasound examination and it was compared with the histopathological report of the hysterectomy specimen. Results: In this study the most common preoperative diagnosis for hysterectomy was fibroid uterus (39%) among which 94.87% showed positive correlation with HPE. Correlation for adenomyosis was 100% between preoperative diagnosis and HPE outcome. Correlation for DUB was poor. 57.14% of the preoperatively diagnosed DUB cases showed adenomyosis on HPE. One case of fibroid showed adenocarcinoma of endometrium on HPE. Conclusions: The study fulfills the aim of finding the efficacy of clinical and USG findings in diagnosing gynecological disorders accurately. Clinical examination is not always adequate. USG is the most important, simple and easily accessible investigation. There is one missed malignant case in this study which is a major shortcoming of clinical evaluation.